Performances of Elementary Pupils in French and Mathematics and Socio-Professional Category and the Formal Education Level of Parents in Togo - TCHABLE Boussanlègue; HOULOUM Biriziwè; MEWEZINO Esso-Mondjonna; AMOUZOU Essè (Universitas Bengkulu, 2021)
This study aims at verifying whether there is a relationship between the academic performance of primary school pupils and the socio-professional category of their parents on the one hand, and the formal educational level of the latter on the other hand. The method used to achieve this double objective combines quantitative and qualitative approaches. Thus, 561 primary elementary pupils from six schools in the Savannahs region participated in the quantitative survey by means of a questionnaire and 35 individual interviews were carried out with teachers and parents of pupils. The data collected was subjected to statistical processing using SPSS 20.0 software and content analysis. The results show that the parents' socio-professional category and school performance are related. Likewise, the best pupils’ performances, both in French and in Mathematics, are obtained by pupils whose parents have a higher level of education.